Beware the villainess! 7 - Soda Ice; Béri (Ize Press, 2026)
"As Melissa suspected, there has been a mysterious being pulling the strings all along. And frustrated by the derailment of their ideal romantasy plot, the entity decides to take a more direct measure. The final battle has begun! Thankfully, all Melissa has to do is sit back and let the dashing men do all the work...or that would've been the case if she hadn't been forced to knock them down a few pegs! With the male leads nowhere at the level they were in the original story, the villainess is once again forced to take matters into her own hands."--Publisher.